Optimalisasi Waktu Produksi Wine Rack Terhadap Permintaan Ekspor Pada PT. Alis Jaya Ciptatama Dengan Menggunakan Metode PERT - Novi Ria Rahmawati; Shinta Murti Scholastika (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
The timeliness achieved by producers in meeting market demand will reflect that character. Through this research, the company can realize the optimal time to meet market demand and export demand. The study conducted this research with the production time required by the company in producing wine rack products to export demand. The data processing method uses network analysis with the PERT (Program Evaluation Review Technique) method. The application of the PERT (Program Evaluation Review Technique) method describes the steps used to determine the critical path of a series of production processes. Then through the known critical path, the time needed to complete the production process can be optimized properly. Through this research, it was found that the wine rack production process at PT. Alis Jaya Ciptatama has 9 (nine) main stages, all of which are included in a series of critical paths. For 1 (one) wine rack that requires a completion time of 785 hours with a probability level of 80,5%.